Feasibility, safety, and early outcomes of direct carotid artery stent implantation with use of the FilterWire EZ Embolic Protection System - Veselka, Josef; Cerná, Daniela; Zimolová, Petra; Martinkovicová, Lucie; Fiedler, Jirí; Hájek, Petr; Malý, Martin; Zemánek, David; Duchonová, Radka (Catheterization and cardiovascular interventions, 2009)
OBJECTIVES: To report on early outcomes of prospective single-center registry, which evaluated feasibility, safety, and effectiveness of direct carotid stenting using FilterWire EZ Embolic Protection System in high-risk patients. BACKGROUND: Little is known about the use of direct carotid stenting with FilterWire EZ Embolic Protection System and different carotid stents. METHODS: Between September 2005 and August 2008, 176 consecutive patients (70 +/- 9 years, 36% symptomatic, 89% at high risk) underwent 214 direct carotid artery stenting procedures with FilterWire EZ Embolic Protection System and different carotid stents. This study included both symptomatic (>or=50% carotid artery stenosis) as well as asymptomatic (>or=70% carotid artery stenosis) patients. The primary endpoint was the rate of 30-day adverse events, defined as neurological death, stroke, or myocardial infarction. RESULTS: We implanted 218 stents (55% with closed cell design) in 214 procedures. The technical success rate of direct stenting was 96%. Carotid artery stenosis before and after direct carotid artery stenting were 82% +/- 10% and 10% +/- 13%, respectively. The median of fluoroscopic time was 6 min (range 2.5-31.5 min). There were two (0.9%) minor strokes and one (0.5%) myocardial infarction within 30 post-procedural days; the primary endpoint occurred in three patients (1.4%). Two patients expired from nonneurological causes unrelated to carotid stenting. CONCLUSION: Direct carotid stenting with FilterWire EZ Embolic Protection System is feasible and safe. Short-term results with respect to neurological events are acceptable.
Keywords: balónková angioplastika; senioři; Prosthesis Design; Embolism; stupeň závažnosti nemoci; Stroke; senioři nad 80 let; Time Factors; výsledek terapie; Middle Aged; registrace; mužské pohlaví; infarkt myokardu; Prospective Studies; studie proveditelnosti; Registries; cévní mozková příhoda; protézy - design; Myocardial Infarction; Angioplasty, Balloon; Aged, 80 and over; ženské pohlaví; Humans; prospektivní studie; stenóza arteria carotis; časové faktory; stenty; lidé středního věku; Stents; Carotid Stenosis; Female; Aged; Severity of Illness Index; Treatment Outcome; Feasibility Studies; embolie; lidé; Male